Malaysia pension fund performances and Islamic vs conventional fund performances - Kong, William Choon San (2018)
Many earlier studies have discussed the performances of conventional funds and Islamic funds. However, there are only few studies have empirically examined on the Pension fund performances and can large pension fund such as Malaysia Employees Provident Fund (EPF) able to outperform the market. Hence to help in filling this gap in empirical literature, this paper attempt to examine the performances of Malaysia pension fund, EPF against Malaysia market index. To examine the performances of EPF, Treynor and Mazuy market timing model is adapt. By using Treynor and Mazuy model, we get to figure out on the EPF Jensen alpha or its selective ability and the fund timing ability. To document the performances of EPF, a time series data from 1986 to 2016 are collected. The variable collected are the yearly dividend of EPF, Malaysia market index (KLCI), and Malaysia government bond which represent the risk free rate. Our empirical result shows that there a strong significant Jensen alpha in the regression while for the market timing ability shows a weak significant and a non-significant beta for market premium. While the second part of this paper shows an empirical testing on the performances of Islamic fund with conventional fund. Many studies have examine the relationship between Islamic fund and conventional fund however there are only few studies which empirically examine the performances of Islamic fund and conventional fund in Malaysia. A panel data were collected from 2014 to 2017 on monthly basis with 28 Islamic and conventional funds. The result shows that based on the average return, risk, and beta, the result shows that Islamic funds outperform the conventional funds. However for Sharpe, Treynor and Jensen Alpha, more conventional funds able to beat its respective market than Islamic funds. This might due to the poor performance of conventional index as a benchmark for conventional funds.